RISK FACTORS ANALYSIS OF HEARING DISORDERS DUE TO NOISE ON MACHINERY WORKERS AT UNIVERSAL STEEL FACTORY - Elvira Kesuma; Muhammad Edy Syahputra Nasution (Universitas Muhammadiyah Sumatera Utara, 2019)
Abstract: Noise, being one of the threats towards occupational health, has exposed 600 million workers globally. The incidence of hearing loss caused by workplace noise is 16% in adults. There are various risk factors of hearing loss. The purpose of this study was to determine the effect of those risk factors on Universal Steel Factory’s workshop workers. This is an analytical study with a cross-sectional design. Data were collected through history taking, physical examination and pure tone audiometry for 30 workers. The data obtained were analyzed using Chi-square and Fisher's exact. There was a correlation between hearing loss with age (p = 0.001), working period (p = 0.001), noise intensity (p = 0.004), and smoking habits (p = 0.013). Therefore, age, working period, noise intensity, and smoking habits have influences to the occurrence of noise-induced hearing loss.Keywords: risk factors, noise-induced hearing loss, workshop workers